The role of mass media in communicating climate science: An empirical evidence - Junsheng, Ha; Akhtar, Rulia; Masud, Muhammad Mehedi; Rana, Md Sohel; Banna, Hasanul (Elsevier, 2019)
World leaders signed the Paris Agreement in 2015 to keep global temperatures well below 2 °C. This Paris Agreement will facilitate achieving Sustainable Development Goal-13 (Climate Action) by 2030. However, without collective action, it is quite impossible to achieve the terms of this agreement. In this regard, the mass media can contribute to making people aware of the subsequent effect of climate change at all levels. The mass media, as a source of information, might play a significant role in raising public awareness and understanding of climate sciences. This paper examines the influence of the mass media on awareness, attitudes and knowledge of climate change, which may lead to environmentally friendly behaviour. This paper employs structural equation modelling to examine the relationship among the studied variables. The results reveal that the mass media influences awareness, attitudes and knowledge of climate change. This study also finds mediating effects of awareness, attitudes and knowledge of climate change between the mass media and environmentally friendly behaviour. The results imply that the mass media contributes to creating awareness, enhancing understating and shaping favourable attitudes towards climate change. The findings could guide policymakers to take appropriate steps to promote a greater awareness of climate change using the mass media. © 2019